Come now, let us reason together - Njoroge, Nyambura (Missionalia: Southern African Journal of Mission Studies, 2001)
The HIV/AIDS pandemic in Africa and other major socio-economic problems call for critical reflection on how communities can be equipped and encouraged to confront these life and community destroying calamities.
Free